Trade reform and quality upgrading in South Africa: A product-level analysis - Kwarambo, Marko (International Food Policy Research Institute, 2013)
The relationship between trade liberalization and product quality is both empirically and theoretically ambiguous. This paper empirically investigates the impact of tariff liberalization on product quality upgrading in the South African manufacturing sector using highly disaggregated product-level data. The study employs panel data techniques exploiting variation at the product level using HS8 product-level data from 1988 to 2009.